Revision of the genus Coccidula Kugelann (Coleoptera, Coccinellidae) - Szawaryn, Karol (Zookeys, 2021)
The genus Coccidula Kugelann includes five species distributed in the Holarctic, with one species in North America and four in Palearctic region. Coccidula belongs to the tribe Coccidulini which historically was treated as a separate subfamily within ladybird beetles, but recent studies confirmed its placement as a tribe within the broadly defined subfamily Coccinellinae. All species are revised and a new synonymy of Lithophilus naviauxi Duverger with C. litophiloides Reitter is proposed. Light and electron microscopy pictures support morphological descriptions. An identification key to all species is also provided.